2020
DOI: 10.1038/s41593-019-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct subgroups of oligodendrocyte precursor cells integrate neural activity and execute myelin formation

Abstract: Recent reports have revealed oligodendrocyte precursor cell (OPC) heterogeneity. It remains unclear if such heterogeneity reflects different subtypes of cells with distinct functions, or rather transiently acquired states of cells with the same function. By integrating lineage formation of individual OPC clones, single-cell transcriptomics, calcium imaging and neural activity manipulation, we show that OPCs in the zebrafish spinal cord can be divided into two functionally distinct groups. One subgroup forms el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
257
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(272 citation statements)
references
References 70 publications
14
257
1
Order By: Relevance
“…Following proliferation, OPCs differentiate into mature oligodendrocytes (Tripathi et al, 2010; Zawadzka et al, 2010). In this study, most oligodendrocytes arose from OPCs that have previously undergone proliferation (Figure 2), similar to OPCs in the developing zebrafish CNS (Marisca et al, 2020). However, this is at variance with the study by Hughes and colleagues (Hughes et al, 2013), who found that in only the minority of events (7 out of 107 cells) did proliferation precede differentiation in the adult cortex.…”
Section: Discussionsupporting
confidence: 57%
“…Following proliferation, OPCs differentiate into mature oligodendrocytes (Tripathi et al, 2010; Zawadzka et al, 2010). In this study, most oligodendrocytes arose from OPCs that have previously undergone proliferation (Figure 2), similar to OPCs in the developing zebrafish CNS (Marisca et al, 2020). However, this is at variance with the study by Hughes and colleagues (Hughes et al, 2013), who found that in only the minority of events (7 out of 107 cells) did proliferation precede differentiation in the adult cortex.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, recent data from Spitzer and colleagues demonstrated that OPCs throughout the brain express a diverse array of electrophysiological properties and ion channels and that these characteristics become more diverse with age 13 . Additionally, data obtained from zebrafish has demonstrated that OPCs can be categorized into two functionally distinct subpopulations that demonstrate different calcium dynamics 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one population of OPCs was found to rarely differentiate in vivo, although these cells maintained their differentiation capacity, indicating that the main functions of this population of OPCs is likely something other than serving as a progenitor pool for mature oligodendrocytes 56 . It is also important to note that both sequencing studies previously mentioned utilized different mouse lines to identify OPCs than the PDGFRα-Cre ER ; R26-EYFP used in this study, which may have also contributed to the difference between our dataset and the previous observations of a homogenous population of OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, how myelination along individual axons is dynamically regulated in intact neural circuits remains unclear, partly due to the difficulty in observing changes to myelin along individual axons over time in vivo. It has been suggested that the synaptic connections that oligodendrocyte progenitor cells (OPCs) can make with axons might transform into myelin sheaths in an activity-regulated manner (19,20), but recent studies have indicated that the OPCs that are synaptically connected to axons are not necessarily those that generate myelinating oligodendrocytes (21). It also remains unclear whether the fusion of synaptic vesicles occurs directly along the axon onto myelin sheaths, or only at synaptic termini, where it would regulate myelination indirectly, for example by spillover onto nearby axonal regions, or by driving changes in parameters such as axonal caliber that could influence myelination.…”
Section: Mainmentioning
confidence: 99%